Motivation as A Mediation of Relationship Between Organizational Culture and Work Environment, Impact on Employee Performance at Bank BJB Surabaya Branch Office - Irene Puspita Dewi; Gendut Sukarno (LPPM of NAROTAMA UNIVERSITY, 2021)
BANK BJB SURABAYA BRANCH OFFICE is an institution engaged in financial services. In carrying out their functions and duties, the leaders and employees of the Bjb Surabaya Branch Office help the individual performance of their employees, but there are recommendations for uneven employee performance results based on preliminary research, it is very important and necessary to conduct research related to the influence of organizational culture and work environment using motivation as a variable. intervention on employee performance.This study aims: 1) To analyze the influence of organizational culture on employee performance at Bank bjb Surabaya Branch Office; 2) To analyze the effect of work environment on employee performance at Bank bjb Surabaya Branch Office; 3) To analyze the influence of organizational culture through motivation on employee performance at Bank bjb Surabaya Branch Office; 4) To analyze the influence of work environment through motivation on employee performance at Bank bjb Surabaya Branch Office.The sample in this study were all leaders and employees of bank bjb Surabaya branch, totaling 59 leaders and employees. The sampling technique used in this study is a sampling technique because the sample under study is part of the entire population. The data analysis technique in this study used the Partial Least Square (PLS) methods.The results of the study concluded that: 1) Organizational culture can contribute to employee performance; 2) The work environment can contribute to employee performance; 3) Organizational culture can contribute to employee performance through motivation; 4) The work environment has not been able to contribute to employee performance through motivation.